Violence Against Women and Girls : Introduction - Gennari, Floriza; McCleary-Sills, Jennifer; Hidalgo, Nidia (World Bank, Washington, DC, 2015)
Violence against women and girls (VAWG) is one of the most oppressive forms of gender inequality and stands as a fundamental barrier to equal participation of women and men in social, economic, and political spheres. Such violence impedes gender equality and the achievement of a range of development outcomes. VAWG is a complex and multifaceted problem that cannot effectively be addressed from a single vantage point. The prevention of, and response to, such violence requires coordinated action across multiple sectors. This resource guide was developed through a partnership between the Global Women s Institute (GWI) at George Washington University, the Inter-American Development Bank (IDB), and the World Bank Group (WBG). The primary audiences for the guide are IDB and WBG staff and member countries, as well as other development professionals who do not yet have experience addressing VAWG. The purpose of this guide is to provide the reader with basic information on the characteristics and consequences of VAWG, including the operational implications that VAWG can have in several priority sectors of the IDB and WBG. It also offers guidance on how to integrate VAWG prevention and provide quality services to violence survivors across a range of development projects. Lastly, it recommends strategies for integrating VAWG prevention and response into policies and legislation, as well as sector programs and projects.